Miunças 5. Avulsos da História Moderna. Instituições, Pessoas e Conflitos - Joaquim Romero Magalhães (Investigação, 2019)
Some less extensive articles and works that were understood to deserve representation received the designation of miunças. The fourth of these compilations is now in the public, which is reserved for the Avulses of modern history: institutions, people and conflicts. It gathers writings dated from 1973 to 2016, which is imagined that they maintain the coherence of the historiographical thought of the author. With special attention to the social aspects of the policies that were undertaken by kings and lords from the end of the 15th century to the 18th century. D. Manuel, D. João III, D. Sebastião deserve some attention. As deserves the daring navigator that was Vasco da Gama or the prelate illustrious that was D. Jerónimo Osório. There are also some issues concerning the Inquisition and the Restoration of the independence of 1640 (and its antecedents). The aim is to analyze some social aspects, which are not strictly political or merely generators of conflicts. Synthesis of military and diplomatic history was reserved for another confrontation, the war of the succession of Spain, with which opened the 18th century peninsular. Which has not only had effects in Europe but has greatly impacted in South America, on the borders between the Portuguese and Spanish colonial domains. Also Brazil of the second half of the same century is a little more known, with the attempt to cover the action of Francisco Xavier de Mendonça Furtado as governor of Grão-Pará and Maranhão. The policy, in relation to the practice of specialized mathematical knowledge, is still marked by the study on the demarcation of the borders of Mato Grosso. Out of research, and just the result of a reflection on geography and history, have gathered yet to this set. A useful divagings in a term of dedication to the knowledge in which both subjects were central.